Management of groundnut diseases through organic amendments, bio products and biocontrol agents: Management of groundnut diseases through organic amendments, bio products and biocontrol agents - D S KELAIYA; K L DOBARIYA (Journal of Oilseeds Research, 2020)
Field experiments were conducted at the Main Oilseeds Research Station, Junagadh Agricultural university,Junagadh (Gujarat) during kharif for three consecutive seasons to evaluate the efficacy of application of organicamendments enriched with biological control agents and application of biological control agents and bio-product as foliar spray in managing soil borne as well as foliar diseases of groundnut. Pooled analysis of the data of three years revealed that the management of collar rot (1.80 %) and stem rot incidence (1.52%) was obtained in the treatment where Trichoderma harzianum was used as a seed treatment@ 10 g/kg seed along with its furrow application @ 4 kg enriched in FYM @ 300 kg/ha at the time of sowing.